Louis-Joseph Papineau’s Seigneurialism, Republicanism, and Jeffersonian Inclinations - Guimond, Olivier (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2021)
Historians have acknowledged that Louis-Joseph Papineau’s political ideas were closely related to Jeffersonian republicanism, but no extensive analysis of this relation has yet been provided. Papineau’s fundamental position on seigneurialism has often been reduced to a supposedly egoistic refusal to endorse the abolition of seigneurial property envisioned by Patriotes in 1838. As close readings of Papineau’s correspondence and speeches reveal, his seigneurialism may be understood in light of his admiration of Jefferson and long-term inclinations for Jeffersonian republicanism. The seigneurial regime, for Papineau, was consistent with what he perceived to be the egalitarian nature of New World societies, such as Lower Canada. It also acted as a system of “free” land distribution, which, in turn, favoured the settlement of independent and virtuous citizens on whom could rest a democratic republic. Moreover, Papineau viewed seigneurialism as a good way to prepare Canadians for integration into a continental American republican society by helping preserve the highly moral character of their nationalité. Papineau’s republican seigneurialism, far from representing a paradoxical stance, was a unique form of “local” republicanism deeply rooted in a French Canadian institution and a “universal” republican ideal.